Consumer's Guide to Regulatory Impact Analysis: Ten Tips for Being an Informed Policymaker. Issue 2 (27th July 2017) - Dudley, Susan; Belzer, Richard; Blomquist, Glenn; Brennan, Timothy; Carrigan, Christopher; Cordes, Joseph; Cox, Louis A.; Fraas, Arthur; Graham, John; Gray, George; Hammitt, James; Krutilla, Kerry; et al.
Abstract : Regulatory impact analyses (RIAs) weigh the benefits of regulations against the burdens they impose and are invaluable tools for informing decision makers. We offer 10 tips for nonspecialist policymakers and interested stakeholders who will be reading RIAs as consumers. 1. Core problem: Determine whether the RIA identifies the core problem (compelling public need) the regulation is intended to address. 2. Alternatives: Look for an objective, policy-neutral evaluation of the relative merits of reasonable alternatives. 3. Baseline: Check whether the RIA presents a reasonable "counterfactual" against which benefits and costs are measured. 4. Increments: Evaluate whether totals and averages obscure relevant distinctions and trade-offs. 5. Uncertainty: Recognize that all estimates involve uncertainty, and ask what effect key assumptions, data, and models have on those estimates. 6. Transparency: Look for transparency and objectivity of analytical inputs. 7. Benefits: Examine how projected benefits relate to stated objectives. 8. Costs: Understand what costs are included. 9. Distribution: Consider how benefits and costs are distributed. 10. Symmetrical treatment: Ensure that benefits and costs are presented symmetrically.